Impact of Total Laboratory Automation on Turnaround Times for Urine Cultures and Screening Specimens for MRSA, ESBL, and VRE Carriage: Retrospective Comparison With Manual Workflow - Cherkaoui, Abdessalam; Renzi, Gesuele; Martischang, Romain; Harbarth, Stephan; Vuilleumier, Nicolas; Schrenzel, Jacques (Frontiers in Cellular and Infection Microbiology, 2020)
Using computerized time-stamps, we compared the turnaround-times (TAT) for urine samples and screening ESwabs of MRSA, VRE and ESBL carriage in the bacteriology laboratory of Geneva University Hospitals between January and December 2017 (period preceding the implementation of the WASPLabTM) with the same specimen types analyzed between January and December 2019 (period after the implementation of the automation). During both one-year periods, a total of 98’380 specimens were analyzed (48’158 in 2017 vs. 50’222 in 2019). On the WASPLabTM, all culture plates were imaged at defined intervals each day of incubation, but the processing of the cultures (i.e., pathogen identification and antimicrobial susceptibility testing) was only performed during day shift hours (approximately 8:00 AM to 4:30 PM). The median TAT for negative reports decreased by almost half for urine samples from 52.1 h (2017) to 28.3 h (2019) (p<0.001), and for MRSA screening specimens from 50.7 h to 26.3 h (p<0.001). The difference in median TAT for negative reports was less pronounced for screening of ESBL (50.2 h versus 43.0 h) (p<0.001) and VRE (50.6 h versus 45.7 h) (p<0.001). Despite a trend towards shorter result delivery for positive samples, there was no significant change in the median TAT. These results suggest that TAT for negative samples immediately benefit from automation, whereas TAT for positive samples also depend on the laboratory hours of operation and daily human resource management.